Groin wound infection in vascular surgery: A one year institutional incidence - Teixeira,Gabriela (2015)
Introduction/Objectives: Surgical site infection (SSI) in vascular surgery is a complication that may lead not only to healing problems, but also limb loss and risk of death. The incidence of surgical site infection at the groin after vascular procedures ranges among 3% to 44%. The aim of this study is to review the incidence of groin infection in our department and the degree of correlation between infection, known risk factors and preventing measures. Methods: Retrospective review of consecutive arterial vascular surgeries in a university central hospital during one year. Patients undergoing groin incisions were studied according to baseline demographics, clinical characteristics, active infection, previous inguinal access, antithrombotic therapy, indication for intervention, prophylactic antibiotic use, type of intervention and type of graft used. Wound site infections over a 30-day period were registered and graded based on Szilagyi classiﬁcation. On patients with documented groin infection, the presentation timing, modality of treatment (surgical and non-surgical) and time of healing were recorded. Data were analyzed by using SPSS 18.0 version software. Results: From January to December 2013, 1266 vascular surgeries were performed. Of these, 782 were arterial vascular procedures, 279 by inguinal approach, with a total of 358 groin incisions. Our base population included 241 patients (31 patients with more than one procedure in a year). Total infection rate was 4.7% (17/358 groin incisions). All Szilagyi I (n = 4) resolved with antibiotic only; three of the ten Szilagyi II infections needed drainage/debridement at operation room; the other Szilagyi II resolved with antibiotic and wound care. All Szilagyi III infections (n = 3) were treated with bypass removal, and in two patients an in situ revascularization was performed. These two patients died from sepsis. Identiﬁcation of the infecting agent was possible in 9 patients, with the most common isolated agent being Pseudomonas. Hypertension was signiﬁcantly associated with a higher risk of SSI (p = 0.033). Discussion/Conclusions: In our department, the infection rate of the inguinal approach equals the best international standards described. These results may be the outcome of a carefully planned strategy of infection control. Arising from the fact that groin SSI is a low incidence event, correlations between suspected risk factors and this infection are hard to establish. Longer follow-ups would be useful for identiﬁcation of all groin infections.